Pengawasan Terhadap Penjual Bensin Eceran Di Kota Ambon - Santri Hairu Letahiit; Julista Mustamu; Merlien Irene Matitaputty (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Retail gasoline sellers are gasoline traders in retail with the object of goods being premium gasoline and pertalite.Purposes of the Research: This study aims to find out and examine how to supervise retail gasoline sellers in Ambon City. Methods of the Research: This writing was carried out with the type of normative juridical research, namely research carried out to obtain data through library studies, namely various literature and scientific materials, and so on. In the normative juridical approach, the data are obtained by using various thoughts of experts and legal theories and existing literature.Results of the Research: Retail gasoline sales are easily found in various district-based areas as well as in cities, even though there are already many gas stations in urban areas, especially in Ambon city. This phenomenon becomes very interesting if one looks at the substance of the Oil and Gas Law, which states clearly that someone who wants to run a business or sell gasoline must have a permit from the government, which of course must go through a strict verification and administrative process. But in reality on the ground, this is really not as it should be, most of the retail gasoline sellers do not have a license or business certificate.